TMOD-06. CREATION OF PATIENT-DERIVED LOWER GRADE GLIOMA ORGANOID MODELS FOR PERSONALIZED TREATMENT RESPONSE ASSESSMENT. (12th November 2021) - Abdullah, Kalil; Buehler, Joseph; Bird, Cylaina; Savani, MIlan; Sternisha, Alex; Levitt, Michael; Hatanpaa, Kimmo; Richardson, Timothy; McBrayer, Samuel
Abstract: Creating in vitro models of lower grade glioma represents a major challenge in neuro-oncology research. There are few such models that are tractable and widely used, which has hindered understanding of the biology of these tumors. Recently, substantial progress has been made in generating patient-derived in vitro organoid models of high grade glioma, but modeling lower grade disease remains difficult. Based on our experience creating neurosphere cultures of lower grade astrocytomas from genetically engineered mice, we hypothesized that modifying patient-derived organoid generation protocols to incorporate physiological oxygen levels would allow establishment and propagation of lower grade glioma organoids. In this study, we show that this approach supports efficient organoid model generation from primary glioma specimens across all histological subtypes and tumor grades (WHO Grade I-IV, n = 20). These organoid models retain key characteristics of their respective parental tumors, including IDH mutations and other genetic alterations, metabolite profiles, intratumoral heterogeneity, cellular composition, and cytoarchitectural features. Importantly, lower grade glioma organoids can be cultured for months and reanimated after biobanking. Our high success rate ( >90%) in establishing organoid models from primary lower grade glioma tissue samples further highlighted opportunities for treatment response assessments. To perform longitudinal measurements of therapy-induced changes in glioma organoid viability, we designed a novel, non-invasive imaging assay (termed rapid apex imaging) to determine real-time treatment response in low and high grade gliomas. We evaluated longitudinal responses of glioblastoma and IDH1 R132H-positive Grade II astrocytoma organoids to temozolomide and olaparib with and without radiation treatment. We quantified topological changes in organoid structure by building a bioinformatics tool to translate imaging data into a cellularity metric as a biomarker of organoid response. Our work unveils an effective new method to create in vitro, personalized models of lower grade glioma that supports elucidation of treatment sensitivity profiles.